PENDEKATAN KOMPLEMENTER DALAM MENGELOLA KELELAHAN PADA PASIEN CHRONIC KIDNEY DISEASE (CKD) PASKA PROSEDUR HEMODIALYSIS: SCOPING REVIEW - Muhammad Irham Ilahia; Satriya Pranata (CV. Denasya Smart Publisher, 2025)
Introduction: Fatigue is a common, persistent, and significant secondary symptom in Chronic Kidney Disease (CKD) patients undergoing Hemodialysis (HD) as renal replacement therapy. This symptom substantially lowers patients' quality of life and is an urgent nursing problem. Although conventional management is pharmacological, non-pharmacological complementary interventions are increasingly considered as safe and effective adjuvant therapies. Scientific evidence regarding the types and effectiveness of these interventions remains scattered. Objective: This study aims to explore and synthesize the literature on the types and effectiveness of complementary therapies used as interventions to reduce fatigue in CKD patients after hemodialysis procedures. Methods: This scoping review was conducted to map the available evidence from four databases (ScienceDirect, PubMed, Garuda, and Scholar). The inclusion criteria were original, full-text, open-access articles published in the last five years (2021–2025) discussing interventions to address post-HD fatigue. Articles that passed the screening were assessed for quality using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. Data synthesis and analysis were performed to summarize the findings. Results: Five articles meeting the eligibility criteria were identified and synthesized. Complementary interventions proven effective in reducing post-HD fatigue include: Intradialytic Exercise, Relaxation Exercise, Foot Reflexology, smartphone-based Recreational Therapy, and a combination of Lavender Aromatherapy with Slow Deep Breathing. Intradialytic Exercise showed the highest effectiveness, with up to an 81% reduction in fatigue symptoms when performed aerobically (>20 minutes during the first 2 hours of the HD session). Relaxation Exercise also showed a huge effect size. The mechanisms of effectiveness for these interventions involve improved blood circulation, reduced stress and muscle tension, and improved energy balance. Conclusion: There is strong evidence for the effectiveness of various types of non-pharmacological complementary therapies as adjunct treatments in the management of fatigue in post-hemodialysis CKD patients. Integrating these interventions, particularly Intradialytic Exercise and Relaxation Exercise, is recommended to be included in routine nursing care protocols to enhance the quality of life for HD patients..